Contribution of small mammal taphonomy to the last Neanderthal occupations at the El Salt site (Alcoi, southeastern Spain). (September 2021) - Marin-Monfort, María Dolores; Fagoaga, Ana; García-Morato, Sara; Ruíz Sánchez, Francisco Javier; Mallol, Carolina; Hernández, Cristo; Galván, Bertila; Fernández-Jalvo, Yolanda
Abstract: The El Salt site (Alcoi, Alicante, Spain) is one of the latest Neanderthal sites in the south-eastern Iberian Peninsula. The disappearance of this human group is controversial and needs detailed studies from different research areas. Taphonomy is essential to establish how representative is a fossil assemblage of the past living organisms that produced it and to interpret the formation process of the fossil site. In the case of El Salt, we have analyzed the micromammal assemblages of Units X and V, which contain fossils of Neanderthals and/or evidence of their activity. In contrast with previous identifications of the little owl ( Athene noctua ), our detailed taphonomic study shown here allows us to conclude that the main predator involved in the production of the micromammal assemblages was the European eagle owl ( Bubo bubo ). This is an opportunistic predator whose feeding preferences and behavior reflect the abundance of local micromammalian species, which can therefore provide a representation of past ecosystems near El Salt. The taphonomic information provided by this study also indicates the absence of transport and reworking processes, and reinforces previous paleoecological interpretations, suggesting an increase of aridity at the top of El Salt sequence that coincided with the local disappearance of Neanderthals.